2018
DOI: 10.21597/jist.412070
|View full text |Cite
|
Sign up to set email alerts
|

Kadmiyum ile Oksidatif Strese Maruz Kalan Sıçanların Beyin Dokusunda Astaksantinin Etkisi;Biyokimyasal, Histopatolojik Değerlendirme

Abstract: Aim of this study is to evaluate protective impact of Astaxanthin (AST) on rats with experimental brain injury induced with Cadmium (Cd). 32 male Wistar albino rats were divided into four groups as Control, Cadmium, Astaxanthin (AST), Cadmium (Cd)+Astaxanthin (AST). Rat brain tissues were obtained at the end of 30 th day. Malondialdehyde (MDA), glutathione (GSH) levels and superoxide dismutase (SOD) enzyme activities were measured in brain homogenates and histopathological examination was performed. MDA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…It has been demonstrated that treading rats with astaxanthin (25 mg kg −1 body weight) five times a week for four weeks, with simultaneous administration of high doses of doxorubicin (8 mg kg −1 body weight in total for 4 weeks), an anti-cancer agent with proven neurotoxic properties, resulted in improvement of cerebral oxidative stress parameters (Table 1), while behavioral tests demonstrated that the treatment significantly improved memory, restored the histopathological architecture of the hippocampus, limited oxidative and inflammatory damage, and reduced the increase in acetylcholinesterase activity [115]. An increase in GSH and SOD, and a decrease in MDA levels in the brains of rats poisoned with Cd was reported by Akkoyun et al [114]. In a study by Wang et al [175], a positive influence of astaxanthin was observed rats whose serum contained elevated levels of homocysteine, which increases the risk of neurodegenerative diseases.…”
Section: Vitamins and Provitaminsmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been demonstrated that treading rats with astaxanthin (25 mg kg −1 body weight) five times a week for four weeks, with simultaneous administration of high doses of doxorubicin (8 mg kg −1 body weight in total for 4 weeks), an anti-cancer agent with proven neurotoxic properties, resulted in improvement of cerebral oxidative stress parameters (Table 1), while behavioral tests demonstrated that the treatment significantly improved memory, restored the histopathological architecture of the hippocampus, limited oxidative and inflammatory damage, and reduced the increase in acetylcholinesterase activity [115]. An increase in GSH and SOD, and a decrease in MDA levels in the brains of rats poisoned with Cd was reported by Akkoyun et al [114]. In a study by Wang et al [175], a positive influence of astaxanthin was observed rats whose serum contained elevated levels of homocysteine, which increases the risk of neurodegenerative diseases.…”
Section: Vitamins and Provitaminsmentioning
confidence: 60%
“…The number of conjugated double bonds in these molecules corresponds to their effectiveness in trapping ROS [167]. Astaxanthin (3,30-dihydroxy-β, β-carotene-4,40-dione) is a red pigment belonging to the sub-class of xanthophyllic carotenoids; it is found mainly in microalgae, mushrooms, and complex plants, as well as in salmon, trout, and crustacean cells [114]. Astaxanthin shows strong antioxidative properties and can neutralize singlet oxygen and free radicals, thus, preventing lipid peroxidation [173].…”
Section: Vitamins and Provitaminsmentioning
confidence: 99%
“…[29] SOD is an enzyme that scavenges peroxide anion radicals and prevents lipid peroxidation caused by free radicals. [23] In this study, while it was observed that the SOD and CAT enzyme activity levels in the KBrO 3 group were significantly reduced compared to the control group, administering ARB was induced depression-like behaviors and caused oxidative stress. [30] Dhouibi et al [31] examined neurobehavioral changes induced by chronic exposure to KBrO 3 in rats and reported that exposure to KBrO 3 caused a reduction in SOD and CAT enzyme activity levels.…”
Section: T a B L E 2 Histopathological Scores In Brain Tissuementioning
confidence: 79%
“…The effects of some drugs, antibiotics, heavy metals and some organic compounds on G6PD and 6PGD enzyme activities have been investigated in the studies conducted so far. In these studies, it was determined that drugs such as netilmicin sulfate, cefepime, amikacin, isepamycin, chloramphenicol, ceftazidim, teicoplanin, ampicillin, ofloxacin, levofloxacin, cefotaxime, penicillin, gentamicin sulfate, ciprofloxacin were determined to inhibit human and rat tissue G6PD and 6PGD enzyme [15,26,[31][32][33][34][35][36]. In the study by Gümüştekin et al, the effects of nicotine and vitamin E on glucose 6-phosphate dehydrogenase (G-6PD) activity in rat muscle, heart, lungs, testes, kidney, stomach, brain and liver tissues were investigated in vivo and in vitro.…”
Section: -Fu [Mm]mentioning
confidence: 99%